Repair of Femoral Capital Physeal Injuries in Cats -14 Cases - Culvenor, J. A.; Black, A. P.; Lorkin, K. F.; Bradley, W. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Femoral capital physeal fractures (CPF) are common injuries in the immature cat. Fractures of the femoral head and neck have been classified by Daly (1) as capital, physeal, subcapital and transcervical. Physeal fractures may also be classified according to Salter (2) and those covered in this paper are Salter I and II.Perez-Aparicio and Fjeld (2) found that many cats become functional without surgical treatment although most developed malunion or non-union. Some of the untreated cats had persistent lameness.While femoral head and neck ostectomy (3), is often recommended and will usually lead to a functional result, particularly in the cat, open reduction and internal fixation is preferred (5, 6) as is recommended in the dog (8, 21).Fourteen femoral capital physeal fractures in 13 cats were repaired with fine pins. The surgical technique and clinical results are described. The authors feel that the ease of the technique and the clinical results make this the treatment of choice for injuries of this type in cats.
Keywords: Hip; feline; capital physeal injury; repair; pins